A Case Report of Sick Sinus Syndrome as an Initial Presentation of Primary Amyloidosis - Abdelazeem, Basel (Cureus, 2021)
Primary light chain amyloidosis (AL amyloidosis) rarely presents as sick sinus syndrome (SSS), and only a few cases have been reported in the literature. A higher index of suspicion is needed to diagnose AL amyloidosis in patients presenting with SSS. Recognizing the electrocardiography (ECG) and transthoracic echocardiogram (TTE) findings for amyloidosis are crucial for early recognition, proper management, and to improve the patients' quality of life. A 79-year-old female initially presented with dyspnea and was diagnosed with SSS that required a pacemaker insertion. Ten days later, the patient had complained of dysphagia and difficulty swallowing. She underwent an esophagogastroduodenoscopy (EGD) to investigate further, and it revealed esophageal and duodenal ulcers, and biopsy was positive for amyloidosis. The patient was worked up for amyloidosis, including bone marrow biopsy, renal biopsy, frees light chains, and serum electrophoresis, which all confirmed the diagnosis of primary amyloidosis. Unfortunately, due to the terminal nature of her condition, the patient was discharged with comfort measures to hospice care.